Optimalisasi Pajak Reklame dalam Meningkatkan Pendapatan Asli Daerah Kota Jakarta Timur - Muhammad Kamaluddin; Tresno Eka Jaya; Ayatulloh Michael Musyaffi (LPPM Universitas Negeri Jakarta, 2025)
This study aims to analyze the growth rate of advertising tax revenue in the Administrative City of East Jakarta during 2020–2024, examine the advertising tax target-setting process, and identify optimization efforts undertaken by the DKI Jakarta Provincial Revenue Agency (Bapenda). This research employs a descriptive qualitative approach using primary and secondary data. Primary data were obtained through interviews with Bapenda officials, while secondary data were collected from regional revenue reports, regulations, and relevant literature. Data analysis was conducted through data reduction, data presentation, growth rate analysis, and conclusion drawing. The results indicate that advertising tax revenue growth fluctuated during the study period, with an average growth rate of 7.98%, categorized as unsuccessful. The target-setting process is based on applicable regulations, historical realization, and potential calculations. Furthermore, optimization efforts have not been fully implemented, as only four of the six recommended regional tax optimization strategies have been applied.